Ultrasound-induced cavitation enhances the delivery and therapeutic efficacy of an oncolytic virus in an in vitro model. - Bazan-Peregrino, M; Arvanitis, C; Rifai, B; Seymour, L; Coussios, C (2012)
We investigated whether ultrasound-induced cavitation at 0.5 MHz could improve the extravasation and distribution of a potent breast cancer-selective oncolytic adenovirus, AdEHE2F-Luc, to tumour regions that are remote from blood vessels. We developed a novel tumour-mimicking model consisting of a gel matrix containing human breast cancer cells traversed by a fluid channel simulating a tumour blood vessel, through which the virus and microbubbles could be made to flow. Ultrasonic pressures were chosen to maximize either broadband emissions, associated with inertial cavitation, or ultraharmonic emissions, associated with stable cavitation, while varying duty cycle to keep the total acoustic energy delivered constant for comparison across exposures. None of the exposure conditions tested affected cell viability in the absence of the adenovirus. When AdEHE2F-Luc was delivered via the vessel, inertial cavitation increased transgene expression in tumour cells by up to 200 times. This increase was not observed in the absence of Coxsackie and Adenovirus Receptor cell expression, discounting sonoporation as the mechanism of action. In the presence of inertial cavitation, AdEHE2F-Luc distribution was greatly improved in the matrix surrounding the vessel, particularly in the direction of the ultrasound beam; this enabled AdEHE2F-Luc to kill up to 80% of cancer cells within the ultrasound focal volume in the gel 24 hours after delivery, compared to 0% in the absence of cavitation.